Follicular cholangitis mimicking a common bile duct cancer: a case report - Kenji Koneri; Takanori Goi; Hokahiro Katayama; Noriyuki Tagai; Michiaki Shimada; Hidetaka Kurebayashi; Katsuji Sawai; Mitsuhiro Morikawa; Masato Tamaki; Yasuo Hirono; Satomi Hatta; Yoshiaki Imamura; et al. (Surgical Case Reports, 2023)
Abstract Background Follicular cholangitis (FC) is a benign bile duct disease that was first reported 2003. Pathologically, it is characterized by lymphoplasmacytic infiltration with multiple lymphoid follicle formations under the mucosal layer of the biliary tract. However, as this disease is extremely rare, little is known about its etiology and pathogenesis. Case presentation A 77-year-old woman was diagnosed with middle bile duct stenosis and potential increases in alkaline phosphatase (ALP) and γ-glutamyl transpeptidase levels (γ-GTP). Carcinoembryonic antigen (CEA), carbohydrate antigen 19-9 (CA19-9) and IgG4 levels were all within the normal limits. Contrast-enhanced computed tomography (CE-CT) and magnetic resonance imaging (MRI) revealed bile duct dilation from intrahepatic to upper common bile duct and an irregular mass lesion in distal bile duct. Additionally, multiple overlapping leaf-like folds were detected. 18F-fluorodeoxyglucose positron emission tomography–computed tomography (18F-FDG-PET/CT) did not demonstrate fluorodeoxyglucose uptake. Subtotal stomach-preserving pancreaticoduodenectomy with regional lymph node dissection was performed because common bile duct cancer could not be ruled out. The resected specimen showed diffuse homogeneous middle bile duct wall thickening. Microscopically, the lesion exhibited thick fibrosis with several invaded lymphoplasmacytic cells, and lymphoid follicle formations were detected under the mucosal layer. Immunohistochemical staining (IHC) revealed positive for CD3, CD4, CD20 and CD79a, and these findings led to a final diagnosis of FC. The patient has not experienced recurrence to date (42 months postoperatively). Conclusions Currently, accurate preoperative diagnosis of FC is difficult. More cases must be accumulated to generate additional knowledge on its precise diagnosis and proper treatment.